Chrotacumines A-D, chromone alkaloids from Dysoxylum acutangulum - Ismail, Intan Safinar; Nagakura, Yuta; Hirasawa, Yusuke; Hosoya, Takahiro; Mohd Lazim, Mohd Izwan; Lajis, Md. Nordin; Shiro, Motoo; Morita, Hiroshi (American Society of Pharmacognosy & American Chemical Society, 2009)
Four new chromone alkaloids, chrotacumines A-D (1-4), consisting of a 5,7-dihydroxy-2-methylchromone, an N-Me piperidine ring, and an ester side chain were isolated from Dysoxylum acutangulum, and their structures including absolute configurations were elucidated on the basis of spectroscopic data interpretation including 2D NMR, CD spectra, and X-ray analysis. The known compound rohitukine (5) showed moderate cytotoxicity against human HL-60 promyelocytic leukemia and HCT-116 colon cancer cells.